Study on Salting out-Steam Distillation Extraction Technology and Antibacterial Activities of Essential Oil from Cumin Seeds - Hong Zhang; Qing-Ping Hu (Graduate Program of Syiah Kuala University, 2014)
The effects of different factors on the yield of essential oil from were discussed, and the extraction conditions of essential oil from cumin seeds by salting out-steam distillation technology based on single-factor test and orthogonal experiment, as well as its antibacterial activities on several common food spoilage bacteria were studied in this paper. The results showed that, the impact order of the influence factors was liquid/solid ratio distilling time NaCl concentration, and optimized extraction conditions were as follows, liquid to material ratio 15:1, soaking time 1 h, 4% NaCl, steam distilling time 3 h. The yield of essential oil was up to 4.48% under these conditions. The results of antibacterial activity assays showed that the essential oil from cumin seeds exhibited the different antibacterial activities against some food borne pathogens, especially it presented the best inhibitory effect against Bacillus subtilis with the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of 6.25 and 12.5 mg/mL respectively, followed by Staphylococcus albus and Staphylococcus aureus, the lowest for Pseudomonas aeruginosa and Shigella dysenteriae